Reference evapotranspiration estimation by different methods for the sucroenergy sector of Colombia - Christian J. Mendoza C.; Andrés J. Peña Q. (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT In the Colombian Sugarcane Research Center CENICAÑA, efficient use of water is always performed based on estimating reference evapotranspiration. In this method, class A pans have been used to estimate the reference evapotranspiration, which provides a more precise estimate of this important variable for water resource management. The objective of this study was to evaluate different reference evapotranspiration methods for the region of influence of the climatological station of the CENICAÑA experimental station. The class A pan method traditionally used in CENICAÑA was compared with and the Penman-Monteith FAO 56 standard method. The historical series used was from January 1, 1994, to December 31, 2014. The climatic variables were the maximum, mean, and minimum temperatures, the mean relative air humidity, solar radiation, and wind speed at 10 m. Willmott’s coefficients, the confidence index (c), and the root mean squared error were used in the performance evaluation. In the comparison with the Penman-Monteith FAO 56 method, all methods presented performance below the minimum requirement of (c) = 0.400. When all methods were compared with the method used in CENICAÑA (Class A pan), only the Penman-Monteith FAO 56 method showed performance classified as good (c = 0.689).